Rapid diagnosis of lymphocytic meningitis by frequency-pulsed electron capture gas-liquid chromatography: differentiation of tuberculous, cryptococcal, and viral meningitis. - Craven, R B (1977)
Cerebrospinal fluid specimens from patients with tuberculous (17 cases), cryptococcal (15 cases), and viral (14 cases) meningitis were analyzed by frequency-pulsed electron capture gas-liquid chromatography and mass spectrometry. Compounds that disappeared after therapy were found to be present in each of these specimens and were not detected in controls. They occurred in repetitive patterns such that these three types of meningitis could be rapidly distinguished. The compound associated with tuberculous meningitis has been tentatively identified. These finding have implications for rapid diagnosis, pathophysiological studies, and possible new therapeutic approaches.